Can we expect an increased suicide rate due to Covid-19?. (21st December 2020) - Devitt, Patrick
Abstract : Human disasters come in all shapes and sizes including wars, terrorist violence, natural events, economic recessions and depressions as well as infection. As a species more fragile than we often allow, humans would be expected to adversely react to these types of disasters in terms of mental ill health and possibly suicidal behaviour leading to increased demands on the Mental Health services. This narrative historical paper examines relevant studies into how previous disasters affected mental health and suicidal behaviour. The characteristics of what is known of the current Covid-19 disease are analysed and compared to other types of disasters with a view to gaining some insight into what we might expect. Of all the types of disasters, economic recession appears most toxic. Mitigating the worst effects of recession appears to be protective. Particularly vulnerable groups are identified in whom we might expect an increase in suicidal behaviour.